2022
DOI: 10.3390/molecules27227846
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Volatilomic Profile of Three Finger Lime (Citrus australasica) Cultivars Based on Chemometrics Analysis of HS-SPME/GC–MS Data

Abstract: Finger lime is receiving growing attention as an ingredient of gastronomic preparations of haute cuisine for its delicious flavor and fragrance and for its appealing aspect. Volatile compounds play a crucial role in determining the organoleptic characteristics of the fruit and its pleasantness for consumers. The aim of the present study was to investigate the volatile profiles by headspace solid phase micro-extraction (HS-SPME) coupled to gas chromatography–mass spectrometry (GC–MS) in the peel and, for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In particular, citronellal was the most relative abundant monoterpene hydrocarbon detected in the peel (23.47%), followed by limonene, citronellol, and linalyl acetate (12.99%, 10.65%, and 7.65% respectively). An inverse citronellal/limonene ratio was registered for the peel of the investigated cultivar compared to the studies reported in the literature [ 5 , 8 ]. Differently, the pulp of the fruit highlighted the main content of linalyl acetate and limonene (18.23% and 11.40%, respectively), along with a higher content of trans -piperitol (1.83%) conferring the typical hint of paper to the culinary used pulp, compared to the peel, in contrast with Cioni et al, 2022 [ 9 ].…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…In particular, citronellal was the most relative abundant monoterpene hydrocarbon detected in the peel (23.47%), followed by limonene, citronellol, and linalyl acetate (12.99%, 10.65%, and 7.65% respectively). An inverse citronellal/limonene ratio was registered for the peel of the investigated cultivar compared to the studies reported in the literature [ 5 , 8 ]. Differently, the pulp of the fruit highlighted the main content of linalyl acetate and limonene (18.23% and 11.40%, respectively), along with a higher content of trans -piperitol (1.83%) conferring the typical hint of paper to the culinary used pulp, compared to the peel, in contrast with Cioni et al, 2022 [ 9 ].…”
Section: Resultsmentioning
confidence: 61%
“…Monoterpenes were the most abundant VOCs identified, followed by sesquiterpenes. Generally, a citronellal/limonene/linalyl acetate chemotype can be considered for the investigated cultivar, highlighting differences in abundance ratios with previous studies [ 5 , 9 ]. The occurrence of linalyl acetate was reported for the first time in Faustrime.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…C. australasica has a high natural genetic diversity with a large number of VOC in different cultivars having β-citronellol, citronellal, γ-terpinene, and limonene as the predominant constituents [ 68 , 69 ]. A previous study has shown that C. australasica is rich in VOC such as citronellal, nonanal, β-phellandrene, δ-elemene, α-farnesol, β-farnesol which can act as antimicrobial agents to provide the plants with resistance against HLB.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of high-value chemical substances from fruit peels can not only effectively alleviate this problem, but can also achieve sustainable development and promote economic cycles [31]. D-limonene is widely present in essential oils extracted from the peels and leaves of natural plants and its content depends on the plant species and cultivar [32][33][34][35]; notably, D-limonene is present in large amounts (up to 98.54%) in citrus (Table 1). Natural plant extraction of D-limonene can be performed using organic solvent extraction, new bio-based solvent extraction, and natural deep eutectic solvent extraction [36][37][38].…”
Section: Natural Plant Extraction: Adding Value To Wastementioning
confidence: 99%